(untitled) (Philological Studies, 2019)
This text examines the different perspectives and interpretations of the relation between the exile and the language. It evolves from the connection between language and the modes of perception of the world and the Other, about which Azade Seyhan has written, it reflects on the notions of Hans-Georg Gadamer and Emmanuel Levinas, and also, it analyzes Amin Maalouf ‘s stance on language as one of the constitutive elements of identity. Later the text focuses on the transformative dimension that results from the relation between exile and language, and its effects. This phenomenon is presented through the notions of Leszek Kolakowski, Czeslaw Milosz, Nina Berberova, Edward Said and Joseph Brodsky, writers who understood exile as a linguistic event.